1994
DOI: 10.1042/bj3010335
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the optical absorption and magnetic-circular-dichroism spectra of peanut peroxidase: electronic structure of a peroxidase with biochemical properties similar to those of horseradish peroxidase

Abstract: The electronic structures of the cationic isoenzyme of peanut peroxidase, horseradish peroxidase (isoenzyme C) and bovine liver catalase are compared through analysis of their optical absorption and magnetic c.d. (m.c.d.) spectral properties. The spectral data for the native resting states and compounds I and II of peanut peroxidase (PeP) are reported. The absorption and m.c.d. data for the native PeP exhibit bands characteristic of the high-spin ferric haem. The absorption spectrum of PeP compound I closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It may seem counterintuitive that heme removal enhances the oxidation susceptibility of cyt c , considering the capability of metal centers to catalyze oxidation. ,, However, metal catalysis is not the only factor that is relevant in this context. CD spectroscopy revealed that heme removal causes cyt c unfolding (Figure S4), confirming earlier reports that the protein structural integrity is contingent on heme .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may seem counterintuitive that heme removal enhances the oxidation susceptibility of cyt c , considering the capability of metal centers to catalyze oxidation. ,, However, metal catalysis is not the only factor that is relevant in this context. CD spectroscopy revealed that heme removal causes cyt c unfolding (Figure S4), confirming earlier reports that the protein structural integrity is contingent on heme .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some protein oxidation events are catalyzed by transition metals. , Fenton-like reactions take place in the presence of peroxides, such as Fe­(II) + H 2 O 2 → Fe­(III) + • OH + OH – . Subsequent metal reduction regenerates Fe­(II) such that the process can continue, generating a steady supply of • OH radicals that attack the protein. ,, The peroxidase activity of some heme proteins represents another metal-catalyzed process. In this case, H 2 O 2 reacts with Fe­(III) heme to form “Compound I”, an Fe­(IV)O species with an adjacent radical. The abstraction of hydrogen from R-H sites then regenerates Fe­(III) .…”
mentioning
confidence: 99%
“…2) [8]. It is also on the order of that observed for 5-coordinate horseradish and peanut peroxidases [20], although the Sorer MCD intensities of peroxidases are slightly more intense a factor we attribute to the strongly hydrogen-bonded histidine/histidinate 5th ligand (Andersson, L.A., in prep.). The Sorer MCD data for the three catalases are clearly considerably weaker in intensity than that typically observed for a 6-coordinate high-spin ferric heme, having water bound axially, of which metaquoMyoglobin is the best known example (e.g.…”
Section: La Anderson Et Al/febs Letters 370 (1995) 97-100mentioning
confidence: 86%
“…The optical detection of the final catalysate has a close relation with the sensitivity of this proposed POD detection system [ 26 , 27 ]. The optical system consisted of three parts: (1) the optical detector (USB 4000, Ocean Optics, Dunedin, FL, USA) for collecting the absorption spectra of the final catalysate, (2) the LED light source with a power of 1 W for providing the incident light, and (3) the Z-type brown flow cell working as both the flow channel and the optical channel.…”
Section: Methodsmentioning
confidence: 99%